The Fz-Dsh Planar Cell Polarity Pathway Induces Oriented Cell Division via Mud/NuMA in Drosophila and Zebrafish. - Ségalen, M.; Johnston, C.A.; Martin, C.A.; Dumortier, J.G.; Prehoda, K.E.; David, N.B.; Doe, C.Q.; Bellaïche, Y. (Developmental Cell, 2010)
The Frizzled receptor and Dishevelled effector regulate mitotic spindle orientation in both vertebrates and invertebrates, but how Dishevelled orients the mitotic spindle is unknown. Using the Drosophila S2 cell "induced polarity" system, we find that Dishevelled cortical polarity is sufficient to orient the spindle and that Dishevelled's DEP domain mediates this function. This domain binds a C-terminal domain of Mud (the Drosophila NuMA ortholog), and Mud is required for Dishevelled-mediated spindle orientation. In Drosophila, Frizzled-Dishevelled planar cell polarity (PCP) orients the sensory organ precursor (pI) spindle along the anterior-posterior axis. We show that Dishevelled and Mud colocalize at the posterior cortex of pI, Mud localization at the posterior cortex requires Dsh, and Mud loss-of-function randomizes spindle orientation. During zebrafish gastrulation, the Wnt11-Frizzled-Dishevelled PCP pathway orients spindles along the animal-vegetal axis, and reducing NuMA levels disrupts spindle orientation. Overall, we describe a Frizzled-Dishevelled-NuMA pathway that orients division from Drosophila to vertebrates.